Despicable me presents Minion madness - Segel, Jason, 1979-; Brand, Russell, 1975-; Carell, Steve, 1963-; Universal Studios Home Entertainment (Firm) (Universal City, CA : Universal Studios Home Entertainment, 2010)
"3 new mini-movies starring the Minions, created exclusively for DVD."
Orientation day -- Home makeover -- Banana.
Special features: the voices of Despicable me; super silly fun land.
Voices: Jason Segel, Russell Brand, Steve Carell, Will Arnett, Julie Andrews.
Not rated.
DVD; various aspect ratios; Dolby Digital 5.1 surround, 2.0 Dolby Digital; dual layer, NTSC, region 1.
English audio track, with optional French or Spanish subtitles; English subtitles for the deaf and hard of hearing.
Keywords: Orphans -- Juvenile films; Good and evil -- Juvenile films